The Contribution of Social Forestry to Proklim: A Case Study In Kapuas Hulu and Sintang, West Kalimantan Province - Bambang Tri Sasongko Adi; Oman Sukmana; Vina Salviana Darvina Soedarwo (Green Publisher Indonesia, 2025)
This study aims to explore the contribution of the Social Forestry (SF) Program in Sustainable Forestry Awards (PROKLIM) in 11 villages in Kapuas Hulu and Sintang, West Kalimantan Province. The focus of the research involves villages that have received PROKLIM awards from the Ministry of Environment and Forestry (MoEF), with the hope that the findings can guide similar implementations in other locations. These villages are the target villages of the FIP-1 Project, which is a collaboration between the Ministry of Environment and Forestry (MoEF) and the Asian Development Bank (ADB). The research methods used were case studies and literature studies, with a descriptive analysis approach. The results show two important aspects: first, there is a significant link between the SF program and PROKLIM assessment criteria, indicating that the existence of SF can positively support and facilitate PROKLIM assessment. Second, of the 15 villages facilitated to apply for PROKLIM, five villages achieved the MAIN PROKLIM Award, four of which had social forestry groups, while ten villages achieved the MADYA PROKLIM with all villages getting social forestry approvals. The research conclusions highlight the need for future PROKLIM development strategies. Such strategies include encouragement of climate-friendly economic activities, partnership building, market development, and community capacity building. The implications of this research can serve as a foundation for interested parties, including the government and related institutions, in designing more effective policies to support social forestry and sustainability efforts in the context of PROKLIM in the West Kalimantan region.